Design, development and characterization of a nanomagnetic system based on iron oxide nanoparticles encapsulated in PLLA-nanospheres. (January 2015) - Rescignano, N.; González-Alfaro, Y.; Fantechi, E.; Mannini, M.; Innocenti, C.; Ruiz-Hitzky, E.; Kenny, J.M.; Armentano, I.
Graphical abstract: Highlights: Iron oxide nanoparticles were encapsulated in PLLA nanospheres by emulsion process. Innovative multifunctional magnetic nanosystem was developed (IO-NPs@PLLA). Stable and monomodal dispersion in aqueous medium was obtained. IO-NPs@PLLA retain IO-NPs magnetic properties and show hyperthermic efficiency. IO-NPs@PLLA are magneto-active nanosystem suitable for biomedical applications. Abstract: This study describes an innovative strategy to develop advanced multifunctional materials, by embedding magnetic nanoparticles in biodegradable poly(l -lactide) (PLLA) nanospheres. The morphology, size distribution and composition of the nanocomposite particles were investigated by several techniques, demonstrating the successful incorporation of the magnetic nanoparticles into monodisperse polymer nanospheres with average diameter of 130 nm. The effect of the encapsulation on the magnetic behaviour was evaluated by magnetometry techniques and the hyperthermic properties of PLLA embedded nanoparticles were investigated. This study suggested that the combination of the hydrophilic, biocompatible polyvinyl alcohol (PVA), used as surfactant, with the biodegradable and biocompatible PLLA and superparamagnetic nanoparticles is a promising strategy worth further implementing to obtain a magneto-active nanocomposite suitable for biomedical applications such as magnetic cell targeting and drug delivery with thermally induced release.